GAMBARAN PENGETAHUAN IBU HAMIL TERHADAP UPAYA PENCEGAHAN STUNTING DI WILAYAH KERJA PUSKESMAS WONOMULYO - Arfan, Farmin; Nur, Hamdan; Ayuni, Sri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
Stunting is still a chronic nutritional problem in Indonesia. This study aimed to describe pregnant women’s knowledge of stunting prevention in the working area of Wonomulyo Health Center. A quantitative descriptive design was used with 39 respondents selected by purposive sampling. Data were collected using questionnaires and analyzed univariately. The results showed that most respondents had good (51.3%), moderate (30.8%), and low (17.9%) knowledge. In conclusion, most pregnant women have good knowledge about stunting prevention, but continuous health education is still needed.